Short-Term Clinical Outcomes After Anterior Cruciate Ligament Reconstruction In Adolescents During The COVID-19 Pandemic - Adam Weaver; Brandon Ness; Dylan Roman; Nicholas Giampetruzzi; Joshua Cleland (International Journal of Sports Physical Therapy)
# Background/Purpose